Analysis of Efficiency of Organic Vegetable Production in Batang Regency Central Java - Sumastuti, Efriyani; Widodo, Wahyu; Sutanto, Himawan Arif (Universitas Negeri Semarang, 2017)
The purpose of this research is to analyze the efficiency level of organic vegetable farming technique in Batang Regency. Twenty seven organic vegetable farmers were taken as samples with saturated samples (census). Stochastic frontier production function has been used to analyze data with the help of frontier 4.1 software. The results of this research indicate that the Efficiency level of organic vegetable farming production in Batang Regency has not been so efficient that there is still a chance to increase the production of organic vegetables. Land area and the use of manure are proved to significantly affect the production of organic vegetables in Batang Regency. Seeds, labor and organic pesticides have no significant effect on the production of organic vegetables in Batang Regency. To increase the efficiency of organic vegetable production in Batang Regency, it is necessary to have the role of stakeholders to provide socialization, mentoring, and facilitation in organic vegetable farming.